Psychopathology and its effect on treatment compliance in pediatric obesity patients - Taner, Yasemen; Törel-Ergür, Ayça; Bahçivan, Gülbağ; Gürdag, Mahinur (The Turkish Journal of Pediatrics, 2009)
Obesity is a common health problem in children and adolescents and has life-threatening physical complications as well as psychological consequences, including negative self-image, low self-esteem and social difficulties. Psychiatric disorders, especially depression and anxiety disorders, are present at higher rates in obese patients. The aim of this study was to investigate the presence and type of psychopathology in a group of obese children and to determine the effect of comorbid psychiatric disorders on treatment compliance. Fifty-four obese patients were evaluated by clinical interviews as well as Schedule for Affective Disorders and Schizophrenia for School-Age Children, Present and Lifetime Version (KIDI-SADS-PL) for psychiatric diagnosis. Fifty percent of the sample was found to have psychopathology and treatment compliance was found to be poor in the group with comorbid psychiatric disorders. This shows that child and adolescent psychiatrists should be included as team members while treating pediatric obese patients.